Aristolochic Acids in the Roots of Aristolochia Chilensis, a Dangerous Chilean Medicinal Plant - Urzua-Moll, A; Santander-Meyer, R; Olguin-Gonzalez, A (Sociedad Chilena de Quimica, 2013)
The chemical composition of aristolochic acids (AAs) from the roots of A. chilensis was determined by high-performance liquid chromatography with diode-array detection (HPLC-DAD), a technique widely used for the detection and quantification of AAs in herbal medicines. The roots contained a mixture of AA-I (1), AA-II (2), AA-III (3), AA-IV (4), AA-Ia (5), AA-IIIa (6), AA-IVa (7), and aristoloside (8), indicating that A. chilensis is not suitable for use as a medicinal plant due to the harmful effects of the aristolochic acids.